Autocracies and Development in a Global Economy: A Tale of Two Elites - Anders Akerman; Anna Larsson; Alireza Naghavi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper studies how comparative advantage and the political elites' endowments shape long-run performance in an economy with imperfect political institutions. In a capital-scarce economy, an autocrat catering to the needs of landowners favours openness to trade at an early stage of development, while an autocrat complying with the preferences of capitalists chooses to shelter the economy from trade. The trade regime interacts with economic institutions, and with policies on capital mobility, to govern capital accumulation. A landed autocrat neglects to improve institutions and blocks foreign capital to maximize extractable rents, leading the economy towards stagnation. By contrast, a capitalist autocrat strengthens institutions, which promotes manufacturing TFP growth, gradually shifts the comparative advantage towards manufacturing and renders the economy attractive to foreign investors. Allowing for trade and foreign capital inflows are thus complementary policies that provide an environment of growth and development in the capital autocracy.
Keywords: F10; F20; P40; P50; O10; O24; 330